Implementation of the Integrated Land and Building Tax Monitoring Module in the Isimu Utara Village Information System, Gorontalo Regency - Wiranto, Ifan; dako, Amirudin Yunus Dako; Nasibu, Iskandar Zulkarnain Nasibu; Dako, Rahmat Deddy Riyanto Dako (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
Penerapan hasil-hasil penelitian dosen serta mahasiswa kepada Masyarakat, merupakan salah satu tujuan dari kegiatan Pengabdian kepada Masyarakat Universitas negeri Gorontalo. Setiap program studi dapat berinovasi untuk mengintegrasikan kegiatan pengabdian masyarakat yang akan dikonversi dengan mata kuliah yang ada pada kurikulum program studi. Berdasarkan hal ini, telah dilakukan kegiatan pengabdian kepada masyarakat di Desa Isimu Utara Kabupaten Gorontalo. Tujuan Pengabdian ini adalah untuk memberikan pembekalan penerapan modul monitoring pajak bumi dan bangunan kepada aparat desa untuk menggantikan sistem monitoring konvensional yang banyak memakan waktu dan tidak efisien. Metode kegiatan Pengabdian Masyarakat menggunakan metode pendampingan dan demonstrasi. Langkah-langkah kegiatan adalah bagaimana penerapan modul monitoring pajak bumi dan bangunan dan dilanjutkan dengan demonstrasi modul aplikasi kepada aparat desa lsimu Utara. Application of the research results of lecturers and students to the community is one of the objectives of Universitas Negeri Gorontalo Service activities. Each study program can innovate to integrate community service activities that will be converted into existing courses in the study program curriculum. Based on this, community service activities have been carried out in Isimu Utara Village, Gorontalo Regency. The aim of this service is to provide guidance on the implementation of the land and building tax monitoring module to village officials to replace the conventional monitoring system which takes a lot of time and is inefficient.Community Service activity methods use mentoring and coercion methods. The activity steps are how to implement the land and building tax monitoring module and continue with finalizing the application module to North Isimu village officials.